Foraging efficiency in Barnacle Geese Branta leucopsis: a functional response to sward height and an analysis of sources of individual variation - Lang, A; Black, J M (Wildfowl, 2001)
The functional response and variation in foraging efficiency of captive Barnacle Geese was measured on pasture sward. Intake rates were calculated for a range of grass sward heights using direct measurements of peck rate, bite height and number of leaves removed with each bite. The functional response was found to be curved reaching a maximum at 85 mm and then declining. Each of the three components of intake rate responded differently to sward height. Peck rate declined steadily with increasing sward height whereas bite height increased throughout the sward heights used. The number of leaves per bite showed a curved response to sward height, increasing to a maximum at sward height of 90 mm then declining. There were significant differences between individuals for bite height and leaves taken per bite. Multiple regression analysis using age, sex, body size and bill size found that 73% of the variation in leaves taken per bite could be explained by the age of the goose, where more leaves were taken per bite by older geese. The results are discussed in relation to other studies on geese foraging on salt-marsh sward and other grazers foraging on pasture.